2002
DOI: 10.1136/ijgc-00009577-200209000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ascites, mass volume, and peritoneal carcinomatosis on serum CA125 levels in patients with ovarian carcinoma

Abstract: Saygili U, Guclu S, Uslu T, Erten O, Dogan E. The effect of ascites, mass volume, and peritoneal carcinomatosis on CA125 levels in patients with ovarian carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
2
4
0
1
Order By: Relevance
“…16 Serum CA-125 levels might be affected by the amount of ascites and the presence of peritoneal carcinomatosis, but not by ovarian mass volume. 17 In the present study, a positive correlation between levels of plasma fibrinogen and serum CA-125 was found in patients with stage II ovarian carcinoma and we, therefore, suggest that fibrinogen is associated with the development of peritoneal carcinomatosis and is not simply the result of increased tumour mass. A positive correlation was not found in stage III and IV patients, which may be due to the more complex nature of advanced states.…”
Section: Discussionsupporting
confidence: 69%
“…16 Serum CA-125 levels might be affected by the amount of ascites and the presence of peritoneal carcinomatosis, but not by ovarian mass volume. 17 In the present study, a positive correlation between levels of plasma fibrinogen and serum CA-125 was found in patients with stage II ovarian carcinoma and we, therefore, suggest that fibrinogen is associated with the development of peritoneal carcinomatosis and is not simply the result of increased tumour mass. A positive correlation was not found in stage III and IV patients, which may be due to the more complex nature of advanced states.…”
Section: Discussionsupporting
confidence: 69%
“…Our data indicated that there was a lower incidence of ovarian clear‐cell carcinoma in the large‐volume ascites group, probably because this histological type is often presented at an early stage 20 . Previous studies reported that serum CA125 levels correlated positively with ascites volume, 21 and this was consistent with our findings. However, a previous retrospective study of 372 patients with EOC showed that the correlation between ascites volume and clinical pathological factors varied with different thresholds 15 …”
Section: Discussionsupporting
confidence: 92%
“…High CA 125 values have been observed in patients with lung, breast, uterine and gastrointestinal tract cancer [11]. Recent study has showed significantly higher serum CA-125 levels in case of ovarian cancer with ascites when compared with those without ascites [12]. Furthermore, it has been reported that some non-malignant diseases, such as chronic liver disease, nephrotic syndrome and chronic renal disease requiring hemodialysis, with concomitant serosal effusions (i.e., fluid accumulation in the pleural, peritoneal or pericardial space) may be associated with elevated serum levels of CA 125 [13][14][15].…”
Section: Discussionmentioning
confidence: 99%